Technology transfer in the agricultural sector: a bibliometric analysis - Cruz-Loaeza, Javier; Arvizu-Barrón, Ezequiel; Alarcón, Alejandro (Revista Mexicana de Ciencias Agrícolas, 2025)
Technology transfer is a process that involves modifying production processes through the conversion, adaptation, or application of innovative ideas, which should generate a benefit for the small producer. This article aims to understand the existing trend of technology transfer in the agricultural sector in the period 2021-2024, through a bibliometric analysis that was divided into two moments: 1) search for information on the Scopus and Web of Science platforms, to later carry it out and 2) construction of the bibliometric map of technology transfer. The findings identified indicate a downward trend in the subject of analysis in 2024 compared to 2023; mixed and quantitative methodologies are the most used to write scientific articles on technology transfer. With the documents analyzed, three thematic groups were identified using the VOSviewer program, where innovation in the agricultural sector accounted for 52% of the analyzed documents and the trend focused on the digitization of the agricultural sector.